Museum audio guides as an accessibility enhancer - Martins, Cláudia (2012)
Accessibility to museums is enhanced by various types of cultural mediation, such as the use of audio guides, which consist of a means for innovative mediation put forth to make the museum visit more autonomous and simultaneously replace the traditional guided visit. Their use is integrated in the tendency for museum democratisation felt in Europe between the 60s and the 80s of the 20th century, especially with the development of educational services at museums and their opening to schools. It is also an invaluable solution for foreign visitors and particularly people with special needs, such as the blind and visually impaired, the deaf and hard-of-hearing or the intellectual disabled. This talk intends to analyse examples of audio guides on offer in Portuguese museums, so as to ascertain the current practices and whether they perform their role as an accessibility tool.